Enhancing English Language Teaching through Digital Transformation in Higher Education: A Case Study of Chiang Rai Rajabhat University - Santhi, Natthaphon; Dawilai, Sirikanya (วารสารสันติศึกษาปริทรรศน์ มจร, 2025)
This study aimed to investigate: 1) the impact of digital transformation on students’ English language proficiency; 2) students’ perceptions of their English language learning through digital platforms; and 3) students’ digital literacy skills in the context of English online learning. The participants were 749 first-year students enrolled in the General English for Communication (GEN2001) course during the first semester of the 2021 academic year. A mixed-methods design was employed, including pre- and post-tests to measure language proficiency and a student satisfaction survey with Likert-scale and open-ended items to assess perceptions and digital literacy. Instruction was delivered using the Bichronous Online Instruction (BOI) model, integrating real-time sessions via Google Meet and Google Classroom with asynchronous tasks on the English Discoveries Online (EDO) platform. The research results were found that: The findings revealed a statistically significant improvement in post-test scores (p < 0.001) and increased student confidence in digital learning. Survey results indicated positive perceptions of the BOI approach, with 82% expressing greater comfort in navigating online platforms. Qualitative responses emphasized engagement, self-paced learning, and motivation, though challenges such as connectivity and the need for guidance were reported. The study recommends optimizing digital tools, enhancing support systems, and refining instructional strategies to promote effective and inclusive digital English language learning.